General Geology of Tronoh Area with an Emphasis on Organic Carbon Distribution - Bin Rosli, Muhammad Rasyidi (Universiti Teknologi PETRONAS, 2014)
The main objective of this research is to determine the Total Organic Carbon of a rock in specific location and organic carbon distribution in Tronoh area. The problem that is need to solved is in Malaysia, oil exploration only focus at offshore whereby at East Coast Malaysia, Sabah and Sarawak offshore. There is no comprehensive onshore analysis and research on hydrocarbon especially on organic carbon distribution. Thus, this project will help in the further analysis in onshore area especially in Tronoh area, Perak. The scope of study is this project is will be conducted in the vicinity of the Tronoh area, in Perak and is based on the outcrops observation and laboratory work. The methodology is by using mapping method and Total Organic Carbon Analysis to find the distribution of organic carbon in Tronoh area.